The Effect of Work Environment, Organizational Culture, and Work Engagement on Work Stress through Workload as a Mediating Variable - Putra, Muhammad Ihsan Sumarlan; Budi Santoso, Anton (UMSurabaya Publishing, 2025)
The enormous scope of management and supervisory tasks by the Bureau of BUMD, Investment, and Development Administration of West Java affects employees' high workload and stress levels. This study aims to determine the impact of the work environment, organizational culture, and work engagement on work stress through employee workload. The sampling technique used was saturated sampling; thus, all 50 employees were used as samples. The data collection technique used a questionnaire, which was then analyzed with SEM using Smart PLS 4.0. The study found that the work environment, organizational culture, engagement, and workload did not affect work stress. In contrast, work engagement significantly positively affected employee work stress. The work environment did not affect workload, while organizational culture positively affected employee workload. The workload could not mediate the influence of the work environment, organizational culture, or work engagement on employee work stress.